Stepping‐up innovations in the water–energy–food nexus: A case study of anaerobic digestion in the UK. Issue 4 (23rd July 2018) - Hoolohan, Claire; Soutar, Iain; Suckling, James; Druckman, Angela; Larkin, Alice; McLachlan, Carly
Abstract : Grand societal challenges such as climate change, poverty and biodiversity loss call for rapid and radical changes to systems of production and consumption. Consequently, there is a growing interest in the dynamics of innovation, both social and technical, to accelerate innovation diffusion so as to increase the possibility of a step‐change or large‐scale transition. Research on the water–energy–food nexus adds an additional dimension to existing discussions, calling for transitions that recognise the sustainability challenges facing three major resource domains, and the synergies and tensions involved in their management. This paper examines anaerobic digestion (AD) – an example of innovation with potential benefits across the water–energy–food nexus – to understand the conditions that influence the rate of AD implementation and the achievement of its potential multi‐sectoral benefits across the water–energy–food nexus. Interview data regarding 15 AD plants are examined alongside complementary data from interviews and workshops using the Technological Innovation Systems framework. This framework provides an analytical structure through which the processes that enable and constrain the implementation of AD in the UK can be examined, enabling the identification of potential mechanisms to support AD's wider and more effective deployment. The findings call for recognition of the unintended consequences of sectoral support mechanisms for technological adaptation, and consequent performance of AD in other resource domains and call for greater integration between policy mechanisms to enable AD to perform across the nexus. They also highlight a need to assimilate knowledge from multiple sources (including site‐specific understanding gained from experimentation) to enhance the base on which policy and decision‐making occurs. These findings contribute to existing literature on sustainable transitions by examining the complexities of multi‐sectoral resource management in the context of nexus research.